Local community knowledge and perceptions in the Colombian Caribbean towards Amphibians in urban and rural settings: tools for biological conservation - Vergara-Rios, Danny; Montes-Correa, Andres Camilo; Urbina-Cardona, J. Nicolas; De Luque-Villa, Miguel; E. Cattan, Pedro; Granda, Hernan Dario (Ethnobiology and Conservation, 2021)
Human perceptions vary between rural and urban environments, determining the degree to which people are able to coexist with biodiversity. It is important to identify the sociodemographic factors that determine these local perceptions to adjust amphibian conservation strategies in recognition of the particular conditions of different human communities. In this research, the effect of the urban or rural location where people live and sociodemographic variables in the knowledge and perceptions about amphibians was determined. The data were collected through individual semi-structured surveys of 401 participants. We measured seven response variables through the Likert scale, which ranges from 1 (totally disagree) to 5 (totally agree). For each response variable, a multivariate analysis of variance was performed. Ninety-two percent of people correctly recognized frogs and toads as amphibians, but there was confusion in classifying caecilians and salamanders within this group or including reptiles within amphibians. This confusion was more evident for women from urban locality. Positive perceptions of amphibians varied between urban and rural locality for young adults, people with a high school education level, and people without formal education. Negative beliefs varied between urban and rural locations for women, adolescents, young adults, and professionals. Half of the people accepted information on the conservation of amphibians. Positive perceptions of people about amphibians should be used as a flag to strengthen environmental educational strategies, mainly in urban locations. The results suggest that amphibian conservation plans that aim to inform and educate the public should be focused differently for age groups, genders, and educational level for people in urban and rural locations.